2017
DOI: 10.35808/ersj/692
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility and Export Volume: The Case of Indonesia and its Main Trading Partners

Abstract: This paper examines the impact of exchange rate volatility on Indonesia's export to-United States, Japan and China using both aggregate and disaggregate data. We first estimated each pair country with export demand equations based on data from 1996 to 2014. A set of export demand equations is estimated by using Seemingly Unrelated Regression to characterized the correlation of the disturbances across equations. In general, the estimation result shows that exchange rate volatility has negative impact on export.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…The aim is to maximize profit through overseas sales (exports). This finding in line with that of Falianty (2015) who found that the elasticity values of the two variables are 0.914 and Safuan (2017) which is around 0.014-0.031. This finding supports the results of Dekle et al (2010) which showed that the elasticity value is between 0.5-0.7.…”
Section: External Variablessupporting
confidence: 92%
“…The aim is to maximize profit through overseas sales (exports). This finding in line with that of Falianty (2015) who found that the elasticity values of the two variables are 0.914 and Safuan (2017) which is around 0.014-0.031. This finding supports the results of Dekle et al (2010) which showed that the elasticity value is between 0.5-0.7.…”
Section: External Variablessupporting
confidence: 92%
“…However, the rubber sector is not the same because of the negative and significant impact that reduces demand in exporting. This result is explained by Ebadi & Ebad (2015) and Safuan (2017) that a country's exports depend on the economy of the destination country. So the demand will continue to increase for certain commodities.…”
Section: Price the Main Condition For Coffee Exports An Analysis With Good News And Bad News Approachesmentioning
confidence: 65%
“…On the other hand, exchange rate volatility had a negative impact on the overall trade volume in India and Pakistan in both the short-run and long-run respectively. Safuan (2017) in another study utilized the Seemingly Unrelated Regression (SUR) methodology and data from 1996-2014 to investigate the effect of exchange rate volatility on exports of Indonesia to Japan, China and the United States (US) employing aggregate and disaggregated data. The findings showed that exchange rate volatility exerted a negative impact on exports.…”
Section: Empirical Literature 211 Empirical Literature For the Rest Of The Worldmentioning
confidence: 99%